Climate of the 21st century: changes and risks - Alfred-Wegener-Institute for Polar and Marine Research (Germany); Research Centre Jülich (Germany); Research Centre for Marine Geosciences (Germany); Max-Planck-Institute for Meteorology (Germany); Potsdam-Institute for Climate Impact Research (Germany); University of Hamburg (Germany); Lozán, José L.; Graßl, Hartmut; Hupfer, Peter (Wissenschaftliche Auswertungen, 2001)
Incl. bibl.